A simplified modal-based method to quantify delamination in carbon fibre-reinforced plastic beam. Issue 3 (3rd July 2019) - Khammassi, Mehdi; Wali, Rizwan; Al-Mutory, Abdulaziz; Yousaf, Arslan; Sassi, Sadok; Gharib, Mohamed
ABSTRACT: This study contributes to our knowledge about the detection and recognition of carbon fibre-reinforced plastic (CFRP) composites by using a modal analysis technique. Delamination was artificially induced during the manufacturing process of CFRP beams so that the dimension and location of the artificial delamination were known. The first three longitudinal bending modes were considered for detecting, locating, and evaluating the delamination. Contrary to what is commonly practised, the sensor placed on the CFRP structure had a large mass in order to contribute actively to restricting the delamination and hence modifying the structure's natural frequencies, thus making it much easier to monitor its health condition. The technique was implemented on a beam with a delamination gap of 9% of the beam's length, positioned within the span of the beam. The results demonstrate that the proposed technique can be effective not only to locate the delamination but also to measure its extent accurately.